Yoga Interventions for Chronic Fatigue Syndrome/Myalgic Encephalomyelitis - A Scoping Review - Giridharan, Selvaraj; Godbole, Mrunmai (International Research Journal of Ayurveda & Yoga, 2025)
Background: Chronic Fatigue Syndrome/Myalgic Encephalomyelitis (CFS/ME) is a debilitating multisystem disorder characterized by persistent fatigue, post-exertional malaise, cognitive impairment, and pain, while also imposing significant socioeconomic burdens. Present treatments are limited, leading to the exploration of complementary therapies, such as yoga, which may affect autonomic function, inflammation, and mental health. This study aimed to map the existing literature on yoga interventions for CFS/ME and identify study designs, interventions, outcomes, and evidence gaps. Materials and Methods: We searched PubMed, Cochrane Library, and Google Scholar from their inception to April 2025 for studies on adults with CFS/ME using yoga. The inclusion criteria encompassed any design that evaluated the effects of yoga on fatigue and its related outcomes. Data were extracted on design, participants, interventions, outcomes, and findings, with the results synthesized narratively and charted. Results: Six primary studies, primarily from a Japanese group, were included. The interventions focused on adapted isometric yoga (sitting/recumbent, 2–3 months, biweekly sessions plus home practice). In some cases, fatigue was consistently reduced with improvements in vigor, pain, depression, autonomic function, and biomarkers (e.g., tumor necrosis factor-α). Adverse events were minor and transient. To date, no qualitative or large-scale studies have been conducted. Conclusions: Adapted isometric yoga shows promise in reducing fatigue in CFS/ME; however, evidence is limited by small samples, single-group designs, and short follow-ups. Larger multicenter randomized controlled studies with standardized protocols and biomarkers are needed to confirm the efficacy and guide its clinical use.